Analysis and use of Cryptography techniques in programming language C#: Coding and Decoding - BAFTIU, Naim (Prizren social science journal, 2020)
Cryptography is an old idea and science, but its approach exists and plays a large role in modernization today. Conventional cryptographic techniques form the basis of today's cryptographic algorithm. The different categories of algorithms have their respective features; internally, in performance and implementation. Cryptographic schemes and mechanisms have undergone continuous improvement. The application of cryptography has grown increasingly, ranging from limited use in state institutions to widespread use by private individuals and companies. The increased use of the Internet has significantly influenced the nature of applications and the way we communicate. Data security dictates the use of different cryptographic techniques. For this reason, we analyze in detail the various coding techniques by evaluating their performance and efficiency. Regarding the new paradigms in cryptography there are also new cryptographic schemes whose application requires detailed study and analysis. The classical cryptography algorithm is the oldest algorithm that was used long before the cryptographic system was discovered. Currently, the system has been widely applied to secure data, and using new methods in a way to improve existing methods. In this thesis the use of cryptographic methods using the C # programming language will be discussed.